High-performance solid waste-based grouting material and preparation method thereof

By using modified blends and functional fillers in the grouting material, the impact of lithium slag powder on the fluidity and performance of the grouting material is solved, and the effects of improving mechanical properties, enhancing durability and optimizing the flowability are achieved.

CN119638312APending Publication Date: 2025-03-18太行城乡建设集团有限公司
View PDF 0 Cites 5 Cited by

Patent Information

Application Number
CN202411766881.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

It is difficult for the prior art to fully utilize industrial solid waste while meeting the basic performance requirements of grouting materials to develop grouting materials with good mechanical properties, strong durability and excellent fluidity.

Method used

Modified blends and functional fillers are used to improve the surface characteristics of lithium slag powder through chemical reactions, reduce its impact on the fluidity of the grouting material, and improve the mechanical properties and durability of the grouting material through the use of functional fillers.

Benefits of technology

The mechanical properties of grouting materials have been improved, durability enhancement and fluidity optimization have been achieved, and the negative impact of lithium slag powder on grouting materials has been solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, and particularly discloses a high-performance solid-waste-based grouting material and a preparation method thereof. Comprising the following raw materials in parts by weight: 32 to 54 parts of Portland cement, 12 to 16 parts of a modified admixture, 2.4 to 3.6 parts of a functional filler, 42 to 56 parts of aggregate, 45 to 55 parts of a photoinitiator solution, 0.6 to 0.8 part of a water reducing agent, 0.9 to 1.1 parts of a composite expanding agent, 0.04 to 0.06 part of a defoaming agent and 9.2 to 12.4 parts of deionized water. Siloxane groups, acylamino groups, ester groups and benzene rings are chemically bonded on the surface of the modified admixture, so that the hydrophilicity of the modified admixture is reduced, the modified admixture can form hydrogen-bond interaction with hydroxyl groups and cement hydrates on the functional filler, and meanwhile, a flexible long-chain alkane structure on the functional filler can be entangled with the modified admixture, so that the flexibility of the modified admixture is improved. The mechanical property, the durability and the fluidity of the grouting material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of building materials, and more specifically, to a high-performance solid waste-based grouting material and a preparation method thereof. Background Art

[0002] Lithium slag and phosphorus slag are industrial waste slags generated in the production of lithium carbonate and steel smelting, respectively. The rational utilization of these waste slags is of great significance for protecting the environment and saving resources. The existing technology mainly treats lithium slag and phosphorus slag by stacking and landfilling, which not only leads to a great waste of resources, but also imposes a heavy burden on the natural environment and land resources. Therefore, it is urgent to make rational resource utilization of lithium slag and phosphorus slag. The amorphous SiO2 and Al2O3 contained in lithium slag have volcanic ash activity. The above raw materials can obtain higher activity under the stimulation of alkaline substances. The glass content in phosphorus slag can generally reach 85-90%, and the main components are CaO and SiO2. They have good activity themselves, so they can be used as mineral admixtures for industrial production of concrete.

[0003] The existing technology mainly focuses on the mechanical properties and workability of grouting materials, and has developed micro-expansion, ultra-high strength, high elastic modulus and ultra-early strength grouting materials. However, lithium slag powder and phosphorus slag powder are porous materials with large internal specific surface areas. When added to the cement-based system, the volume fraction of solid particles in the cement-based system will increase, and the surface of solid particles requires more liquid phase to wet, resulting in reduced fluidity, mechanical properties and durability of the grouting material. Therefore, while meeting the basic performance requirements of the grouting material, making full use of industrial solid waste to develop a grouting material with good mechanical properties, strong durability and excellent fluidity is a technical problem that needs to be solved at present. Summary of the invention

[0004] In order to solve the problems mentioned in the above background technology, the present application provides a high-performance solid waste-based grouting material and a preparation method thereof.

[0005] A high-performance solid waste-based grouting material, comprising the following raw materials in parts by weight: 32-54 parts of silicate cement, 12-16 parts of modified admixture, 2.4-3.6 parts of functional filler, 42-56 parts of aggregate, 45-55 parts of photoinitiator solution, 0.6-0.8 parts of water reducer, 0.9-1.1 parts of composite expansion agent, 0.04-0.06 parts of defoamer and 9.2-12.4 parts of deionized water; The preparation method of the high-performance solid waste-based grouting material comprises the following steps: Step S1, adding silicate cement, modified admixture, functional filler and aggregate into a photoinitiator solution, irradiating with ultraviolet light for 12-16 minutes, controlling the irradiation temperature to 62-66° C., continuing to stir and react for 7-9 hours, and after the reaction is completed, rotary evaporation, washing and drying to obtain monomer A; Step S2, mixing the polycarboxylate water-reducing agent, the composite expansion agent and the defoaming agent and stirring evenly to obtain monomer B; Step S3, mixing monomer A and monomer B, stirring evenly to obtain a premix, adding the premix into deionized water, stirring evenly to obtain a high-performance solid waste-based grouting material.

[0006] Preferably, the aggregate is grade II medium sand with a fineness modulus of 2.9 and a mud content of 1.6%.

[0007] Preferably, the photoinitiator solution is a mixture of benzoin dimethyl ether and cyclohexanone in a mass ratio of 0.4-0.6:100.

[0008] Preferably, the composite expansion agent is a mixture of ettringite and calcium oxide in a mass ratio of 1-2:1.

[0009] Preferably, the modified admixture is prepared by the following steps: Step A1, grinding lithium slag powder and phosphorus slag powder until they pass through a 100-200 mesh sieve, then adding alkali solution, ultrasonically dispersing for 15-35 minutes, washing, and drying to obtain alkali-treated slag powder, wherein the mass ratio of lithium slag powder, phosphorus slag powder, and alkali solution is 2.4-3.2:3.6-4.4:70-80; Step A2, adding alkali-treated slag powder, anhydrous ethanol and KH-560 into deionized water, stirring evenly, heating to 42-46° C., continuing stirring for 5-7 hours, centrifuging, washing and drying the precipitate to obtain epoxy slag powder, wherein the mass ratio of alkali-treated slag powder, anhydrous ethanol, KH-560 and deionized water is 3-4:40-50:14-18:40-60. In the above reaction process, deionized water is used as a solvent, and the active hydroxyl groups on the alkali-treated slag powder and the siloxane groups on the KH-560 undergo a dehydration condensation reaction to obtain epoxy alkali slag powder; Step A3, ultrasonically dispersing epoxy slag powder in anhydrous DMF, dripping tetrabutylammonium bromide, α-acetylaminocinnamic acid and anhydrous DMF mixed solution a, and controlling the dripping to be completed within 10 minutes. After the dripping is completed, the temperature is raised to 90-110°C, and the reaction is stirred for 4-6 hours. After the reaction is completed, centrifugation is performed, and the precipitate is washed and dried to obtain a modified admixture, wherein the mass ratio of epoxy slag powder, anhydrous DMF and mixed solution a is 2.4-2.8:50-60:26-28, and the mass ratio of tetrabutylammonium bromide, α-acetylaminocinnamic acid and anhydrous DMF in the mixed solution a is 0.6-0.8:4.4-5.6:32-36. In the above reaction process, anhydrous DMF is used as solvent and tetrabutylammonium bromide is used as catalyst. The epoxy slag powder and α-acetylaminocinnamic acid undergo a ring-opening esterification reaction to obtain the modified admixture.

[0010] Preferably, the alkali solution is a sodium hydroxide aqueous solution with a mass fraction of 40-50%.

[0011] Preferably, the functionalized filler is prepared by the following steps: Step B1, KH-550, octadecenyl succinic anhydride and isopropanol are mixed uniformly at 35-45°C, the pH is adjusted to 9-10, the temperature is raised to 56-64°C, and stirring is continued for 7-9h to obtain a modified solution, nano-silica is ultrasonically dispersed in anhydrous DMF, the modified solution and deionized water are added, the reaction is stirred for 10-12h, and the filter cake is filtered and washed and dried to obtain carboxylated silica, wherein the mass ratio of KH-550, octadecenyl succinic anhydride and isopropanol is 0.25-0.65:1-2:16-30, and the mass ratio of nano-silica, anhydrous The mass ratio of DMF, modified liquid and deionized water is 3.6-4.4:100-120:32-40:6-14. First, KH-550 and octadecene succinic anhydride are subjected to amidation reaction to obtain modified liquid, and then the modified liquid is used to modify the nano-silica to obtain carboxylated silica containing amide bonds. Through the above reaction, a long alkyl chain with high fat solubility is introduced into the nano-silica, further enhancing the compatibility of silica in asphalt. At the same time, the carboxyl group grafted on the nano-silica through modification can also participate in the subsequent chemical reaction process; Step B2, carboxylated silica, 3-amino-5-mercapto-1,2,4-triazole, N,N-dicyclohexylcarbodiimide and 4-dimethylaminopyridine are added to anhydrous DMF, heated to 35-45°C, stirred evenly, then heated to 76-84°C, stirred for 6-8h, rotary evaporated, washed, and dried to obtain a functional filler, wherein carboxylated silica, 3-amino-5-mercapto-1,2,4-triazole, N,N-dicyclohexylcarbodiimide and 4-dimethylaminopyridine are added to anhydrous DMF, heated to 35-45°C, stirred evenly, then heated to 76-84°C, stirred for 6-8h, rotary evaporated, washed, and dried to obtain a functional filler, wherein carboxylated silica, 3-amino-5-mercapto-1,2,4-triazole, N,N The mass ratio of dicyclohexylcarbodiimide, 4-dimethylaminopyridine and anhydrous DMF is 2.2-3.4:5-6:11-13:4.6-5.6:80-90. In the above reaction process, anhydrous DMF is used as solvent, N,N-dicyclohexylcarbodiimide is used as dehydrating agent, 4-dimethylaminopyridine is used as catalyst, carboxylated silica and 3-amino-5-mercapto-1,2,4-triazole undergo amidation reaction to obtain functionalized filler.

[0012] Compared with the prior art, the present invention has the following beneficial effects: In order to reduce the influence of lithium slag on the fluidity of grouting materials and improve the mechanical properties and durability of grouting materials, this application starts from two aspects. First, modified admixtures are added. The surface of the modified admixtures is bonded with siloxane groups, amide groups, ester groups, and benzene rings on the surface of the alkali-treated slag powder through chemical reactions. The presence of siloxane groups, on the one hand, reduces the hydrophilicity of the alkali-treated slag powder and improves the influence of lithium slag on the fluidity of grouting materials. On the other hand, it can also entangle with the flexible long-chain alkane structure on the functionalized filler to form a mutually entangled molecular interpenetrating network structure, further improving its mechanical properties. The presence of amide groups can form hydrogen bonds with the active hydroxyl groups on the functionalized filler and the hydroxyl groups in the cement hydration products, thereby improving the compatibility between the modified admixture and the functionalized filler and the cement-based material, further improving the mechanical properties of the grouting material. The presence of ester groups exerts its own hydrophobicity and improves the lithium The influence of slag on the fluidity of the grouting material, and it can also have good compatibility with functional fillers with ester structure, further improving the mechanical properties of the grouting material. The presence of benzene ring, on the one hand, exerts its own good chemical stability and improves the durability of the grouting material. On the other hand, it can also produce π-π interaction with the triazole group with good corrosion resistance in the functional monomer, which improves the compatibility of the modified admixture and the functional filler, while further improving the mechanical properties and durability of the grouting material. Secondly, the addition of functional fillers, on the one hand, exerts the good chemical stability of silica itself, on the other hand, the octadecene succinic anhydride grafted on the surface of the functional filler contains unsaturated double bonds, which can chemically bond with the unsaturated double bonds on the functional components. Introducing it into the grouting material can synergize with the functional components to jointly improve the mechanical properties, durability and fluidity of the grouting material. DETAILED DESCRIPTION

[0013] In order to make the implementation methods of the present application easier to understand, the present application will be described in detail below in conjunction with specific examples. These examples are only for illustration and are not limited to the scope of application of the present application.

[0014] The contents of the main raw materials and their components used in the examples and comparative examples are as follows: The silicate cement is PO·42.5 grade ordinary silicate cement produced by Henan Dadi Cement Group, and the chemical composition is shown in Table 1; the polycarboxylic acid water reducer is the PCA-1 series polycarboxylic acid high-performance water reducer produced by Jiangsu Subote New Materials Co., Ltd., which is light brown liquid with a solid content of 15% and a water reduction rate of 25-30%; the defoamer is a polyether concrete defoamer produced by Dongguan Antai Fine Chemical Co., Ltd., model AT1238, and pH value of 6-9; the lithium slag powder is produced by Sichuan Suining Yahua Lithium Industry, and the specific parameters are shown in Table 1; the phosphorus slag powder is produced by Liangshan Ruihai Industry of Gangcheng Group, and the specific parameters are shown in Table 1; Table 1 Main chemical components of grouting materials

[0015] The present application is further described in detail below in conjunction with embodiments and comparative examples.

[0016] Preparation Examples 1-3 and Comparative Preparation Examples 1-2 provide methods for preparing modified admixtures.

[0017] Preparation Example 1 This preparation example provides a modified admixture, which is prepared by the following steps: Step A1, grinding the lithium slag powder and the phosphorus slag powder until they pass through a 100-mesh sieve, then adding a 40% by mass sodium hydroxide aqueous solution, controlling the ultrasonic frequency to 35 kHz, the ultrasonic power to 500 w, the ultrasonic time to 26 min, then washing with anhydrous ethanol and deionized water for 3 times in sequence, and drying at 60° C. to constant weight to obtain an alkali-treated slag powder, wherein the mass ratio of the lithium slag powder, the phosphorus slag powder and the 40% by mass sodium hydroxide aqueous solution is 2.4:3.6:70; Step A2, adding alkali-treated slag powder, anhydrous ethanol and KH-560 to deionized water, stirring at a speed of 600 rpm for 32 minutes until uniform, heating to 42°C, maintaining the speed unchanged, continuing to stir and react for 5 hours, centrifuging, precipitating, and then washing with anhydrous ethanol and deionized water for 3 times in sequence, and drying at 50°C to constant weight to obtain epoxy slag powder, wherein the mass ratio of alkali-treated slag powder, anhydrous ethanol, KH-560 and deionized water is 3:40:14:40; Step A3, ultrasonically disperse the epoxy slag powder in anhydrous DMF, control the ultrasonic frequency to 45kHz, the ultrasonic power to 650W, the ultrasonic time to 36min, drip tetrabutylammonium bromide, α-acetylaminocinnamic acid and anhydrous DMF mixed solution a, control the dripping to be completed within 10min, after the dripping is completed, heat to 90°C, stir and react at a speed of 700rpm for 4h, after the reaction is completed, centrifuge, wash the precipitate with anhydrous ethanol and deionized water for 3 times, and dry at 65°C to constant weight to obtain a modified admixture, wherein the mass ratio of epoxy slag powder, anhydrous DMF and mixed solution a is 2.4:50:26, and the mass ratio of tetrabutylammonium bromide, α-acetylaminocinnamic acid and anhydrous DMF in the mixed solution a is 0.6:4.4:32.

[0018] Preparation Example 2 This preparation example provides a modified admixture, which is prepared by the following steps: Step A1, grinding lithium slag powder and phosphorus slag powder until they pass through a 150-mesh sieve, adding a 45% by mass sodium hydroxide aqueous solution, controlling the ultrasonic frequency to 40 kHz, the ultrasonic power to 550 W, and the ultrasonic time to 30 min, then washing with anhydrous ethanol and deionized water for 4 times in sequence, and drying at 65° C. to constant weight to obtain alkali-treated slag powder, wherein the mass ratio of lithium slag powder, phosphorus slag powder and 45% by mass sodium hydroxide aqueous solution is 2.8:4.0:75; Step A2, adding alkali-treated slag powder, anhydrous ethanol and KH-560 to deionized water, stirring at a speed of 700 rpm for 36 minutes until uniform, heating to 44°C, maintaining the speed unchanged, continuing stirring for 6 hours, centrifuging, precipitating, and then washing with anhydrous ethanol and deionized water for 4 times in sequence, and drying at 55°C to constant weight to obtain epoxy slag powder, wherein the mass ratio of alkali-treated slag powder, anhydrous ethanol, KH-560 and deionized water is 3.5:45:16:50; Step A3, ultrasonically disperse the epoxy slag powder in anhydrous DMF, control the ultrasonic frequency to 40kHz, the ultrasonic power to 600W, the ultrasonic time to 40min, drip tetrabutylammonium bromide, α-acetylaminocinnamic acid and anhydrous DMF mixed solution a, control the dripping to be completed within 10min, after the dripping is completed, heat to 100°C, stir and react at a speed of 750rpm for 5h, after the reaction is completed, centrifuge, wash the precipitate with anhydrous ethanol and deionized water for 4 times, and dry at 70°C to constant weight to obtain a modified admixture, wherein the mass ratio of epoxy slag powder, anhydrous DMF and mixed solution a is 2.6:55:27, and the mass ratio of tetrabutylammonium bromide, α-acetylaminocinnamic acid and anhydrous DMF in the mixed solution a is 0.7:5.0:34.

[0019] Preparation Example 3 This preparation example provides a modified admixture, which is prepared by the following steps: Step A1, grinding lithium slag powder and phosphorus slag powder until they pass through a 200-mesh sieve, adding a 50% by mass sodium hydroxide aqueous solution, controlling the ultrasonic frequency to 45 kHz, the ultrasonic power to 600 w, and the ultrasonic time to 34 min, then washing with anhydrous ethanol and deionized water for 5 times in sequence, and drying at 70° C. to constant weight to obtain alkali-treated slag powder, wherein the mass ratio of lithium slag powder, phosphorus slag powder and 50% by mass sodium hydroxide aqueous solution is 3.2:4.4:80; Step A2, adding alkali-treated slag powder, anhydrous ethanol and KH-560 to deionized water, stirring at a speed of 750 rpm for 40 minutes until uniform, heating to 46°C, maintaining the speed unchanged, continuing stirring for 7 hours, centrifuging, precipitating, and then washing with anhydrous ethanol and deionized water for 5 times in sequence, and drying at 60°C to constant weight to obtain epoxy slag powder, wherein the mass ratio of alkali-treated slag powder, anhydrous ethanol, KH-560 and deionized water is 4:50:18:60; Step A3, ultrasonically disperse the epoxy slag powder in anhydrous DMF, control the ultrasonic frequency to 50kHz, the ultrasonic power to 700W, the ultrasonic time to 44min, drip tetrabutylammonium bromide, α-acetylaminocinnamic acid and anhydrous DMF mixed solution a, control the dripping to be completed within 10min, after the dripping is completed, heat to 110°C, stir and react at a speed of 750rpm for 6h, after the reaction is completed, centrifuge, wash the precipitate with anhydrous ethanol and deionized water for 5 times, and dry at 75°C to constant weight to obtain a modified admixture, wherein the mass ratio of epoxy slag powder, anhydrous DMF and mixed solution a is 2.8:60:28, and the mass ratio of tetrabutylammonium bromide, α-acetylaminocinnamic acid and anhydrous DMF in the mixed solution a is 0.8:5.6:36.

[0020] Comparative Preparation Example 1 This comparative preparation example provides a modified admixture, which is prepared by the following steps: Step A1, grinding the lithium slag powder and the phosphorus slag powder until they pass through a 100-mesh sieve, then adding a 40% by mass sodium hydroxide aqueous solution, controlling the ultrasonic frequency to 35 kHz, the ultrasonic power to 500 w, the ultrasonic time to 26 min, then washing with anhydrous ethanol and deionized water for 3 times in sequence, and drying at 60° C. to constant weight to obtain an alkali-treated slag powder, wherein the mass ratio of the lithium slag powder, the phosphorus slag powder and the 40% by mass sodium hydroxide aqueous solution is 2.4:3.6:70; Step A2, adding alkali-treated slag powder, anhydrous ethanol and KH-560 to deionized water, stirring at a speed of 600 rpm for 32 minutes until uniform, heating to 42°C, maintaining the speed unchanged, continuing to stir and react for 5 hours, centrifuging, precipitating, and then washing with anhydrous ethanol and deionized water for 3 times in sequence, and drying at 50°C to constant weight to obtain epoxy slag powder, wherein the mass ratio of alkali-treated slag powder, anhydrous ethanol, KH-560 and deionized water is 3:40:14:40; Step A3, ultrasonically disperse the epoxy slag powder in anhydrous DMF, control the ultrasonic frequency to 45kHz, the ultrasonic power to 650W, the ultrasonic time to 36min, drip tetrabutylammonium bromide, α-methylcinnamic acid and anhydrous DMF mixed solution a, control the dripping to be completed within 10min, after the dripping is completed, heat to 90°C, stir and react at a speed of 700rpm for 4h, after the reaction is completed, centrifuge, wash the precipitate with anhydrous ethanol and deionized water for 3 times, and dry at 65°C to constant weight to obtain a modified admixture, wherein the mass ratio of epoxy slag powder, anhydrous DMF and mixed solution a is 2.4:50:26, and the mass ratio of tetrabutylammonium bromide, α-methylcinnamic acid and anhydrous DMF in the mixed solution a is 0.6:4.4:32.

[0021] Comparative Preparation Example 2 This comparative preparation example provides a modified admixture, which is prepared by the following steps: Step A1, grinding the lithium slag powder and the phosphorus slag powder until they pass through a 100-mesh sieve, then adding a 40% by mass sodium hydroxide aqueous solution, controlling the ultrasonic frequency to 35 kHz, the ultrasonic power to 500 w, the ultrasonic time to 26 min, then washing with anhydrous ethanol and deionized water for 3 times in sequence, and drying at 60° C. to constant weight to obtain an alkali-treated slag powder, wherein the mass ratio of the lithium slag powder, the phosphorus slag powder and the 40% by mass sodium hydroxide aqueous solution is 2.4:3.6:70; Step A2, adding alkali-treated slag powder, anhydrous ethanol and KH-560 to deionized water, stirring at a speed of 600 rpm for 32 minutes until uniform, heating to 42°C, maintaining the speed unchanged, continuing to stir and react for 5 hours, centrifuging, precipitating, and then washing with anhydrous ethanol and deionized water for 3 times in sequence, and drying at 50°C to constant weight to obtain epoxy slag powder, wherein the mass ratio of alkali-treated slag powder, anhydrous ethanol, KH-560 and deionized water is 3:40:14:40; Step A3, ultrasonically disperse the epoxy slag powder in anhydrous DMF, control the ultrasonic frequency to 45kHz, the ultrasonic power to 650w, the ultrasonic time to 36min, add tetrabutylammonium bromide, 3-methylbutenoic acid and anhydrous DMF mixed solution a dropwise, after the addition is completed, heat to 90°C, stir and react at a speed of 700rpm for 4h, after the reaction is completed, centrifuge, wash the precipitate with anhydrous ethanol and deionized water for 3 times, and dry at 65°C to constant weight to obtain a modified admixture, wherein the mass ratio of epoxy slag powder, anhydrous DMF and mixed solution a is 2.4:50:26, and the mass ratio of tetrabutylammonium bromide, 3-methylbutenoic acid and anhydrous DMF in the mixed solution a is 0.6:4.4:32.

[0022] Preparation Examples 4-6 and Comparative Preparation Examples 3-4 provide methods for preparing functionalized fillers.

[0023] Preparation Example 4 This preparation example provides a functionalized filler, which is prepared by the following steps: Step B1, KH-550, octadecenyl succinic anhydride and isopropanol were stirred at a speed of 600 rpm and 35° C. for 30 min until uniform, the pH was adjusted to 9 with a 0.4 M sodium hydroxide aqueous solution, the temperature was raised to 56° C., the speed was maintained unchanged, and stirring was continued for 7 h to obtain a modified solution, nano-silicon dioxide was ultrasonically dispersed in anhydrous DMF, the ultrasonic frequency was controlled to 40 kHz, the ultrasonic power was 550 w, the ultrasonic time was 35 min, the modified solution and deionized water were added, the speed was controlled to 700 rpm, the reaction was stirred for 10 h, and the filter cake was washed with anhydrous ethanol and deionized water for 3 times, and dried at 55° C. to constant weight to obtain carboxylated silica, wherein the mass ratio of KH-550, octadecenyl succinic anhydride and isopropanol was 0.25:1:16, and the mass ratio of nano-silicon dioxide, anhydrous DMF, modified solution and deionized water was 3.6:100:32:6; Step B2, carboxylated silica, 3-amino-5-mercapto-1,2,4-triazole, N,N-dicyclohexylcarbodiimide and 4-dimethylaminopyridine are added to anhydrous DMF, the temperature is raised to 45°C, the speed is controlled to be 700rpm and stirred for 26min until uniform, the temperature is then raised to 76°C, the speed is maintained unchanged, and the stirring reaction is continued for 6h, and the anhydrous DMF is removed by rotary evaporation, the rotary evaporation temperature is controlled to be 82°C, and then washed with anhydrous ethanol and deionized water for 3 times in sequence, and dried at 60°C to constant weight to obtain a functionalized filler, wherein the mass ratio of carboxylated silica, 3-amino-5-mercapto-1,2,4-triazole, N,N-dicyclohexylcarbodiimide, 4-dimethylaminopyridine and anhydrous DMF is 2.2:5:11:4.6:80.

[0024] Preparation Example 5 This preparation example provides a functionalized filler, which is prepared by the following steps: Step B1, KH-550, octadecenyl succinic anhydride and isopropanol are stirred at a speed of 650 rpm and 40° C. for 35 min until uniform, the pH is adjusted to 9.5 with a 0.6 M sodium hydroxide aqueous solution, the temperature is raised to 60° C., the speed is maintained unchanged, and stirring is continued for 8 h to obtain a modified solution, the nano-silicon dioxide is ultrasonically dispersed in anhydrous DMF, the ultrasonic frequency is controlled to 35 kHz, the ultrasonic power is 500 w, the ultrasonic time is 40 min, the modified solution and deionized water are added, the speed is controlled to 750 rpm, the reaction is stirred for 11 h, and the filter cake is washed and dried to obtain carboxylated silica, wherein the mass ratio of KH-550, octadecenyl succinic anhydride and isopropanol is 0.45:1.5:23, and the mass ratio of nano-silicon dioxide, anhydrous DMF, modified solution and deionized water is 4.0:110:36:10; Step B2, carboxylated silica, 3-amino-5-mercapto-1,2,4-triazole, N,N-dicyclohexylcarbodiimide and 4-dimethylaminopyridine are added to anhydrous DMF, the temperature is raised to 40°C, the speed is controlled to be stirred at 720rpm for 28min until uniform, the temperature is raised to 80°C, the stirring reaction is continued for 7h, the anhydrous DMF is removed by rotary evaporation, the rotary evaporation temperature is controlled to 84°C, and then washed with anhydrous ethanol and deionized water 4 times in sequence, and dried at 65°C to constant weight to obtain a functionalized filler, wherein the mass ratio of carboxylated silica, 3-amino-5-mercapto-1,2,4-triazole, N,N-dicyclohexylcarbodiimide, 4-dimethylaminopyridine and anhydrous DMF is 2.8:5.5:12:5.1:85.

[0025] Preparation Example 6 This preparation example provides a functionalized filler, which is prepared by the following steps: Step B1, KH-550, octadecenyl succinic anhydride and isopropanol were stirred at a speed of 700 rpm and 45° C. for 40 min until uniform, the pH was adjusted to 10 with a 0.8 M sodium hydroxide aqueous solution, the temperature was raised to 64° C., the speed was maintained unchanged, and stirring was continued for 9 h to obtain a modified solution, nano-silicon dioxide was ultrasonically dispersed in anhydrous DMF, the ultrasonic frequency was controlled to 45 kHz, the ultrasonic power was 600 w, and the ultrasonic time was 45 min, the modified solution and deionized water were added, the speed was controlled to 800 rpm, the reaction was stirred for 12 h, and the filter cake was washed with anhydrous ethanol and deionized water for 5 times, and dried at 65° C. to constant weight to obtain carboxylated silica, wherein the mass ratio of KH-550, octadecenyl succinic anhydride and isopropanol was 0.65:2:30, and the mass ratio of nano-silicon dioxide, anhydrous DMF, modified solution and deionized water was 4.4:120:40:14; Step B2, carboxylated silica, 3-amino-5-mercapto-1,2,4-triazole, N,N-dicyclohexylcarbodiimide and 4-dimethylaminopyridine are added to anhydrous DMF, the temperature is raised to 45°C, the speed is controlled to be stirred at 740rpm for 30min until uniform, the temperature is raised to 84°C, the speed is maintained unchanged, and the stirring reaction is continued for 8h, and the anhydrous DMF is removed by rotary evaporation, the rotary evaporation temperature is controlled to be 86°C, and then washed with anhydrous ethanol and deionized water for 5 times in sequence, and dried at 70°C to constant weight to obtain a functionalized filler, wherein the mass ratio of carboxylated silica, 3-amino-5-mercapto-1,2,4-triazole, N,N-dicyclohexylcarbodiimide, 4-dimethylaminopyridine and anhydrous DMF is 3.4:6:13:5.6:90.

[0026] Comparative Preparation Example 3 This comparative preparation example provides a functionalized filler, which is prepared by the following steps: Step B1, KH-550, itaconic anhydride and isopropanol were stirred at a speed of 600 rpm and 35° C. for 30 min until uniform, the pH was adjusted to 9 with a 0.4 M sodium hydroxide aqueous solution, the temperature was raised to 56° C., the speed was maintained unchanged, and stirring was continued for 7 h to obtain a modified liquid, and the nano-silicon dioxide was ultrasonically dispersed in anhydrous DMF, the ultrasonic frequency was controlled to 40 kHz, the ultrasonic power was 550 w, and the ultrasonic time was 35 min, the modified liquid and deionized water were added, the speed was controlled to 700 rpm, the reaction was stirred for 10 h, and the filter cake was washed with anhydrous ethanol and deionized water for 3 times, and dried at 55° C. to constant weight to obtain carboxylated silica, wherein the mass ratio of KH-550, itaconic anhydride and isopropanol was 0.25:1:16, and the mass ratio of nano-silicon dioxide, anhydrous DMF, modified liquid and deionized water was 3.6:100:32:6; Step B2, carboxylated silica, 3-amino-5-mercapto-1,2,4-triazole, N,N-dicyclohexylcarbodiimide and 4-dimethylaminopyridine are added to anhydrous DMF, the temperature is raised to 45°C, the speed is controlled to be 700rpm and stirred for 26min until uniform, the temperature is then raised to 76°C, the speed is maintained unchanged, and the stirring reaction is continued for 6h, and the anhydrous DMF is removed by rotary evaporation, the rotary evaporation temperature is controlled to be 82°C, and then washed with anhydrous ethanol and deionized water for 3 times in sequence, and dried at 60°C to constant weight to obtain a functionalized filler, wherein the mass ratio of carboxylated silica, 3-amino-5-mercapto-1,2,4-triazole, N,N-dicyclohexylcarbodiimide, 4-dimethylaminopyridine and anhydrous DMF is 2.2:5:11:4.6:80.

[0027] Comparative Preparation Example 4 This comparative preparation example provides a functionalized filler, which is prepared by the following steps: Step B1, KH-550, octadecenyl succinic anhydride and isopropanol were stirred at a speed of 600 rpm and 35° C. for 30 min until uniform, the pH was adjusted to 9 with a 0.4 M sodium hydroxide aqueous solution, the temperature was raised to 56° C., the speed was maintained unchanged, and stirring was continued for 7 h to obtain a modified solution, nano-silicon dioxide was ultrasonically dispersed in anhydrous DMF, the ultrasonic frequency was controlled to 40 kHz, the ultrasonic power was 550 w, the ultrasonic time was 35 min, the modified solution and deionized water were added, the speed was controlled to 700 rpm, the reaction was stirred for 10 h, and the filter cake was washed with anhydrous ethanol and deionized water for 3 times, and dried at 55° C. to constant weight to obtain carboxylated silica, wherein the mass ratio of KH-550, octadecenyl succinic anhydride and isopropanol was 0.25:1:16, and the mass ratio of nano-silicon dioxide, anhydrous DMF, modified solution and deionized water was 3.6:100:32:6; Step B2, add carboxylated silica, 4,6-diamino-2-mercaptopyrimidine, N,N-dicyclohexylcarbodiimide and 4-dimethylaminopyridine to anhydrous DMF, heat to 45°C, control the speed to 700rpm and stir for 26min until uniform, then heat to 76°C, maintain the speed unchanged, continue stirring and react for 6h, remove anhydrous DMF by rotary evaporation, control the rotary evaporation temperature to 82°C, then wash with anhydrous ethanol and deionized water three times in sequence, and dry at 60°C to constant weight to obtain a functionalized filler, wherein the mass ratio of carboxylated silica, 4,6-diamino-2-mercaptopyrimidine, N,N-dicyclohexylcarbodiimide, 4-dimethylaminopyridine and anhydrous DMF is 2.2:5:11:4.6:80.

[0028] Examples 1-3 and Comparative Examples 1-4 provide a high-performance solid waste-based grouting material and a preparation method thereof.

[0029] Example 1 The present embodiment provides a high-performance solid waste-based grouting material and a preparation method thereof. The high-performance solid waste-based grouting material comprises the following raw materials in parts by weight: 32 parts of silicate cement, 12 parts of modified admixture prepared in Preparation Example 1, 2.4 parts of functionalized filler prepared in Preparation Example 4, 42 parts of aggregate, 45 parts of photoinitiator solution, 0.6 parts of polycarboxylic acid water reducer, 0.9 parts of composite expansion agent, 0.04 parts of polyether concrete defoamer and 9.2 parts of deionized water, wherein the photoinitiator solution is a mixture of benzoin dimethyl ether and cyclohexanone in a mass ratio of 0.4:100, and the composite expansion agent is a mixture of ettringite and calcium oxide in a mass ratio of 1:1; The preparation method of the high-performance solid waste-based grouting material comprises the following steps: Step S1: Add silicate cement, modified admixture, functional filler and aggregate into the photoinitiator solution, stir at a speed of 650 rpm for 16 min until uniform, and place under a wavelength peak of 365 nm and an intensity of 80 mw / cm 2 The mixture was irradiated under ultraviolet light for 12 minutes, the irradiation temperature was controlled at 62°C, and the reaction was continued with stirring for 7 hours. After the reaction was completed, the deionized water was removed by rotary evaporation, the rotary evaporation temperature was controlled at 52°C, and then washed with anhydrous ethanol and deionized water for 3 times in sequence, and dried at 50°C to constant weight to obtain monomer A, wherein the aggregate was grade II medium sand, the fineness modulus was 2.9, the mud content was 1.6%, and the photoinitiator solution was a mixture of benzoin dimethyl ether and cyclohexanone at a mass ratio of 0.4:100; Step S2, mixing a carboxylic acid water-reducing agent, a composite expansion agent and a polyether concrete defoaming agent, and stirring at a rotation speed of 300 rpm for 16 minutes until the mixture is uniform, to obtain a monomer B; Step S3, mix monomer A and monomer B, stir at a rotation speed of 560 rpm for 12 minutes to obtain a premix, add the premix into deionized water, stir at a rotation speed of 1100 rpm for 5 minutes until uniform, and obtain a high-performance solid waste-based grouting material.

[0030] Example 2 The present embodiment provides a high-performance solid waste-based grouting material and a preparation method thereof. The high-performance solid waste-based grouting material comprises the following raw materials in parts by weight: 43 parts of silicate cement, 14 parts of modified admixture prepared in Preparation Example 2, 3.0 parts of functionalized filler prepared in Preparation Example 5, 49 parts of aggregate, 50 parts of photoinitiator solution, 0.7 parts of polycarboxylic acid water reducer, 1.0 parts of composite expansion agent, 0.05 parts of polyether concrete defoamer and 10.3 parts of deionized water, wherein the aggregate is grade II medium sand with a fineness modulus of 2.9 and a mud content of 1.6%, the photoinitiator solution is a mixture of benzoin dimethyl ether and cyclohexanone in a mass ratio of 0.5:100, and the composite expansion agent is a mixture of ettringite and calcium oxide in a mass ratio of 1.5:1; The preparation method of the high-performance solid waste-based grouting material comprises the following steps: Step S1: Add silicate cement, modified admixture, functional filler and aggregate into the photoinitiator solution, stir at a speed of 700 rpm for 18 min until uniform, and place under a wavelength peak of 365 nm and an intensity of 80 mw / cm 2 The mixture was irradiated under ultraviolet light for 14 minutes, the irradiation temperature was controlled at 64°C, the rotation speed was maintained unchanged, and the reaction was continued with stirring for 8 hours. After the reaction was completed, the deionized water was removed by rotary evaporation, the rotary evaporation temperature was controlled at 54°C, and then washed with anhydrous ethanol and deionized water for 4 times in sequence, and dried at 55°C to constant weight to obtain monomer A, wherein the photoinitiator solution was a mixture of benzoin dimethyl ether and cyclohexanone in a mass ratio of 0.5:100; Step S2, mixing a polycarboxylate water-reducing agent, a composite expansion agent and a polyether concrete defoaming agent, and stirring at a rotation speed of 350 pm for 18 minutes until the mixture is uniform, to obtain a monomer B; Step S3, mix monomer A and monomer B, stir at a rotation speed of 580 rpm for 14 minutes to obtain a premix, add the premix into deionized water, stir at a rotation speed of 1200 rpm for 6 minutes until uniform, and obtain a high-performance solid waste-based grouting material.

[0031] Example 3 The present embodiment provides a high-performance solid waste-based grouting material and a preparation method thereof. The high-performance solid waste-based grouting material comprises the following raw materials in parts by weight: 54 parts of silicate cement, 16 parts of modified admixture prepared in Preparation Example 3, 3.6 parts of functionalized filler prepared in Preparation Example 6, 56 parts of aggregate, 55 parts of photoinitiator solution, 0.8 parts of polycarboxylic acid water reducer, 1.1 parts of composite expansion agent, 0.06 parts of polyether concrete defoamer and 12.4 parts of deionized water, wherein the aggregate is grade II medium sand with a fineness modulus of 2.9 and a mud content of 1.6%, the photoinitiator solution is a mixture of benzoin dimethyl ether and cyclohexanone in a mass ratio of 0.6:100, and the composite expansion agent is a mixture of ettringite and calcium oxide in a mass ratio of 2:1; The preparation method of the high-performance solid waste-based grouting material comprises the following steps: Step S1: Add silicate cement, modified admixture, functional filler and aggregate into the photoinitiator solution, stir at a speed of 750 rpm for 20 min until uniform, and place under a wavelength peak of 365 nm and an intensity of 80 mw / cm 2 The mixture was irradiated under ultraviolet light for 16 minutes, the irradiation temperature was controlled at 66°C, the rotation speed was maintained unchanged, and the reaction was continued with stirring for 9 hours. After the reaction, the cyclohexanone was removed by rotary evaporation, the rotary evaporation temperature was controlled at 96°C, and then washed with anhydrous ethanol and deionized water for 5 times in sequence, and dried at 60°C to constant weight to obtain monomer A, wherein the photoinitiator solution was a mixture of potassium persulfate and deionized water at a mass ratio of 0.6:100; Step S2, mixing a polycarboxylate water-reducing agent, a composite expansion agent and a polyether concrete defoaming agent, and stirring at a rotation speed of 400 rpm for 20 minutes until the mixture is uniform, to obtain a monomer B; Step S3, mix monomer A and monomer B, stir at a rotation speed of 600 rpm for 16 minutes to obtain a premix, add the premix into deionized water, stir at a rotation speed of 1300 rpm for 7 minutes until uniform, and obtain a high-performance solid waste-based grouting material.

[0032] Comparative Example 1 The present comparative example provides a high-performance solid waste-based grouting material and a preparation method thereof. The high-performance solid waste-based grouting material comprises the following raw materials in parts by weight: 32 parts of silicate cement, 12 parts of modified admixture prepared in comparative preparation example 1, 2.4 parts of functionalized filler prepared in preparation example 4, 42 parts of aggregate, 45 parts of photoinitiator solution, 0.6 parts of polycarboxylic acid water reducer, 0.9 parts of composite expansion agent, 0.04 parts of polyether concrete defoamer and 9.2 parts of deionized water, wherein the aggregate is grade II medium sand with a fineness modulus of 2.9 and a mud content of 1.6%, the photoinitiator solution is a mixture of benzoin dimethyl ether and cyclohexanone in a mass ratio of 0.4:100, and the composite expansion agent is a mixture of ettringite and calcium oxide in a mass ratio of 1:1; The preparation method of the high-performance solid waste-based grouting material comprises the following steps: Step S1: Add silicate cement, modified admixture, functional filler and aggregate into the photoinitiator solution, stir at a speed of 650 rpm for 16 min until uniform, and place under a wavelength peak of 365 nm and an intensity of 80 mw / cm 2 The mixture was irradiated under ultraviolet light for 12 minutes, the irradiation temperature was controlled at 62°C, and the reaction was continued with stirring for 7 hours. After the reaction was completed, the deionized water was removed by rotary evaporation, the rotary evaporation temperature was controlled at 52°C, and then washed with anhydrous ethanol and deionized water for 3 times in sequence, and dried at 50°C to constant weight to obtain monomer A, wherein the photoinitiator solution was a mixture of benzoin dimethyl ether and cyclohexanone at a mass ratio of 0.4:100; Step S2, mixing a polycarboxylate water-reducing agent, a composite expansion agent and a polyether concrete defoaming agent, and stirring at a rotation speed of 300 rpm for 16 minutes until the mixture is uniform, to obtain a monomer B; Step S3, mix monomer A and monomer B, stir at a rotation speed of 560 rpm for 12 minutes to obtain a premix, add the premix into deionized water, stir at a rotation speed of 1100 rpm for 5 minutes until uniform, and obtain a high-performance solid waste-based grouting material.

[0033] Comparative Example 2 This comparative example provides a high-performance solid waste-based grouting material and a preparation method thereof. The high-performance solid waste-based grouting material comprises the following raw materials in parts by weight: 32 parts of silicate cement, 12 parts of modified admixture prepared in comparative preparation example 2, 2.4 parts of functionalized filler prepared in preparation example 4, 42 parts of aggregate, 45 parts of photoinitiator solution, 0.6 parts of polycarboxylic acid water reducer, 0.9 parts of composite expansion agent, 0.04 parts of polyether concrete defoamer and 9.2 parts of deionized water, wherein the photoinitiator solution is a mixture of benzoin dimethyl ether and cyclohexanone at a mass ratio of 0.4:100, and the composite expansion agent is a mixture of ettringite and calcium oxide at a mass ratio of 1:1; The preparation method of the high-performance solid waste-based grouting material comprises the following steps: Step S1: Add silicate cement, modified admixture, functional filler and aggregate into the photoinitiator solution, stir at a speed of 650 rpm for 16 min until uniform, and place under a wavelength peak of 365 nm and an intensity of 80 mw / cm 2 The mixture was irradiated under ultraviolet light for 12 minutes, the irradiation temperature was controlled at 62°C, and the reaction was continued with stirring for 7 hours. After the reaction was completed, the deionized water was removed by rotary evaporation, the rotary evaporation temperature was controlled at 52°C, and then washed with anhydrous ethanol and deionized water for 3 times in sequence, and dried at 50°C to constant weight to obtain monomer A, wherein the photoinitiator solution was a mixture of benzoin dimethyl ether and cyclohexanone at a mass ratio of 0.4:100; Step S2, mixing a polycarboxylate water-reducing agent, a composite expansion agent and a polyether concrete defoaming agent, and stirring at a rotation speed of 300 rpm for 16 minutes until the mixture is uniform, to obtain a monomer B; Step S3, mix monomer A and monomer B, stir at a rotation speed of 560 rpm for 12 minutes to obtain a premix, add the premix into deionized water, stir at a rotation speed of 1100 rpm for 5 minutes until uniform, and obtain a high-performance solid waste-based grouting material.

[0034] Comparative Example 3 This comparative example provides a high-performance solid waste-based grouting material and a preparation method thereof. The high-performance solid waste-based grouting material comprises the following raw materials in parts by weight: 32 parts of silicate cement, 12 parts of modified admixture prepared in Preparation Example 1, 2.4 parts of functionalized filler prepared in Comparative Preparation Example 3, 42 parts of aggregate, 45 parts of photoinitiator solution, 0.6 parts of polycarboxylic acid water reducer, 0.9 parts of composite expansion agent, 0.04 parts of polyether concrete defoamer and 9.2 parts of deionized water, wherein the photoinitiator solution is a mixture of benzoin dimethyl ether and cyclohexanone at a mass ratio of 0.4:100, and the composite expansion agent is a mixture of ettringite and calcium oxide at a mass ratio of 1:1; The preparation method of the high-performance solid waste-based grouting material comprises the following steps: Step S1: Add silicate cement, modified admixture, functional filler and aggregate into the photoinitiator solution, stir at a speed of 650 rpm for 16 min until uniform, and place under a wavelength peak of 365 nm and an intensity of 80 mw / cm 2 The mixture was irradiated under ultraviolet light for 12 minutes, the irradiation temperature was controlled at 62°C, and the reaction was continued with stirring for 7 hours. After the reaction was completed, the deionized water was removed by rotary evaporation, the rotary evaporation temperature was controlled at 52°C, and then washed with anhydrous ethanol and deionized water for 3 times in sequence, and dried at 50°C to constant weight to obtain monomer A, wherein the photoinitiator solution was a mixture of benzoin dimethyl ether and cyclohexanone at a mass ratio of 0.4:100; Step S2, mixing a polycarboxylate water-reducing agent, a composite expansion agent and a polyether concrete defoaming agent, and stirring at a rotation speed of 300 rpm for 16 minutes until the mixture is uniform, to obtain a monomer B; Step S3, mix monomer A and monomer B, stir at a rotation speed of 560 rpm for 12 minutes to obtain a premix, add the premix into deionized water, stir at a rotation speed of 1100 rpm for 5 minutes until uniform, and obtain a high-performance solid waste-based grouting material.

[0035] Comparative Example 4 This comparative example provides a high-performance solid waste-based grouting material and a preparation method thereof. The high-performance solid waste-based grouting material comprises the following raw materials in parts by weight: 32 parts of silicate cement, 12 parts of modified admixture prepared in Preparation Example 1, 2.4 parts of functionalized filler prepared in Comparative Preparation Example 4, 42 parts of aggregate, 45 parts of photoinitiator solution, 0.6 parts of polycarboxylic acid water reducer, 0.9 parts of composite expansion agent, 0.04 parts of polyether concrete defoamer and 9.2 parts of deionized water, wherein the photoinitiator solution is a mixture of benzoin dimethyl ether and cyclohexanone at a mass ratio of 0.4:100, and the composite expansion agent is a mixture of ettringite and calcium oxide at a mass ratio of 1:1; The preparation method of the high-performance solid waste-based grouting material comprises the following steps: Step S1: Add silicate cement, modified admixture, functional filler and aggregate into the photoinitiator solution, stir at a speed of 650 rpm for 16 min until uniform, and place under a wavelength peak of 365 nm and an intensity of 80 mw / cm 2 The mixture was irradiated under ultraviolet light for 12 minutes, the irradiation temperature was controlled at 62°C, and the reaction was continued with stirring for 7 hours. After the reaction was completed, the deionized water was removed by rotary evaporation, the rotary evaporation temperature was controlled at 52°C, and then washed with anhydrous ethanol and deionized water for 3 times in sequence, and dried at 50°C to constant weight to obtain monomer A, wherein the photoinitiator solution was a mixture of benzoin dimethyl ether and cyclohexanone at a mass ratio of 0.4:100; Step S2, mixing a polycarboxylate water-reducing agent, a composite expansion agent and a polyether concrete defoaming agent, and stirring at a rotation speed of 300 rpm for 16 minutes until the mixture is uniform, to obtain a monomer B; Step S3, mix monomer A and monomer B, stir at a rotation speed of 560 rpm for 12 minutes to obtain a premix, add the premix into deionized water, stir at a rotation speed of 1100 rpm for 5 minutes until uniform, and obtain a high-performance solid waste-based grouting material.

[0036] Performance Testing The embodiment was subjected to performance testing, and mechanical and workability tests were performed according to the specifications GB / T 50448-2015 "Technical Specifications for Application of Cement-based Grouting Materials" and JG / T 408-2019 "Sleeve Grouting Materials for Steel Bar Connections". The sulfate erosion resistance test was performed according to the specification GB / T50082-2009 "Test Methods for Long-term Performance and Durability of Ordinary Concrete". After 15 cycles of erosion with a 10% concentration of Na2SO4 solution, the test results are shown in Table 2 below; Table 2 Performance test of solid waste-based grouting materials prepared in Examples 1-3 and Comparative Examples 1-4

[0037] It can be seen from Table 2 that, compared with Comparative Examples 1-4, the solid waste-based grouting materials prepared in Examples 1-3 have better fluidity, mechanical properties and durability.

[0038] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A high-performance solid waste-based grouting material, characterized in that: The invention comprises the following raw materials in parts by weight: 32-54 parts of silicate cement, 12-16 parts of modified admixture, 2.4-3.6 parts of functional filler, 42-56 parts of aggregate, 45-55 parts of photoinitiator solution, 0.6-0.8 parts of water reducing agent, 0.9-1.1 parts of composite expansion agent, 0.04-0.06 parts of defoaming agent and 9.2-12.4 parts of deionized water; The modified admixture is firstly prepared by treating lithium slag powder and phosphorus slag powder with alkali solution to obtain alkali-treated slag powder, then chemically bonding with KH-560 to obtain epoxy slag powder, and then ring-opening esterification with α-acetylaminocinnamic acid to obtain the modified admixture; The functional filler is firstly prepared by chemically bonding KH-550 and octadecene succinic anhydride to obtain a modified liquid, and then the modified liquid is used to modify nano silicon dioxide to obtain carboxylated silicon dioxide, and then the functional filler is prepared by an amidation reaction with 3-amino-5-mercapto-1,2,4-triazole.

2. A high-performance solid waste-based grouting material according to claim 1, characterized in that: The modified admixture is prepared by the following steps: Step A1, grinding lithium slag powder and phosphorus slag powder, passing through a 100-200 mesh sieve, adding alkali solution, ultrasonically dispersing for 15-35 minutes, washing, and drying to obtain alkali-treated slag powder; Step A2, adding alkali-treated slag powder, anhydrous ethanol and KH-560 into deionized water, stirring evenly, heating to 42-46° C., stirring for 5-7 hours, centrifuging, washing and drying the precipitate to obtain epoxy slag powder; Step A3, ultrasonically disperse the epoxy slag powder in anhydrous DMF, and dropwise add tetrabutylammonium bromide, α-acetylaminocinnamic acid and anhydrous DMF mixed solution a, and control the dropping to be completed within 10 minutes. After the dropping is completed, the temperature is raised to 90-110°C, and the reaction is stirred for 4-6 hours. After the reaction is completed, centrifuge, wash the precipitate, and dry it to obtain a modified admixture.

3. A high-performance solid waste-based grouting material according to claim 2, characterized in that: In the step A1, the mass ratio of lithium slag powder, phosphorus slag powder and alkali solution is 2.4-3.2:3.6-4.4:70-80.

4. A high-performance solid waste-based grouting material according to claim 2, characterized in that: In the step A2, the mass ratio of the alkali-treated slag powder, anhydrous ethanol, KH-560 and deionized water is 3-4:40-50:14-18:40-60.

5. The high-performance solid waste-based grouting material according to claim 2, characterized in that: In the step A3, the mass ratio of epoxy slag powder, anhydrous DMF and mixed solution a is 2.4-2.8:50-60:26-28, and in the mixed solution a, the mass ratio of tetrabutylammonium bromide, α-acetylaminocinnamic acid and anhydrous DMF is 0.6-0.8:4.4-5.6:32-36.

6. The high-performance solid waste-based grouting material according to claim 1, characterized in that: The functionalized filler is prepared by the following steps: Step B1, KH-550, octadecene succinic anhydride and isopropanol are mixed uniformly at 35-45° C., the pH is adjusted to 9-10, the temperature is raised to 56-64° C., and stirring is continued for 7-9 hours to obtain a modified solution, nano-silicon dioxide is ultrasonically dispersed in anhydrous DMF, the modified solution and deionized water are added, the reaction is stirred for 10-12 hours, and the filter cake is washed and dried to obtain carboxylated silicon dioxide; Step B2, add carboxylated silica, 3-amino-5-mercapto-1,2,4-triazole, N,N-dicyclohexylcarbodiimide and 4-dimethylaminopyridine to anhydrous DMF, heat to 35-45°C, stir evenly, then heat to 76-84°C, continue stirring to react for 6-8h, rotary evaporate, wash, and dry to obtain a functionalized filler.

7. A high-performance solid waste-based grouting material according to claim 6, characterized in that: In the step B1, the mass ratio of KH-550, octadecenylsuccinic anhydride and isopropanol is 0.25-0.65:1-2:16-30, and the mass ratio of nano-silica, anhydrous DMF, modification liquid and deionized water is 3.6-4.4:100-120:32-40:6-14.

8. The high-performance solid waste-based grouting material according to claim 6, characterized in that: In the step B2, the mass ratio of carboxylated silica, 3-amino-5-mercapto-1,2,4-triazole, N,N-dicyclohexylcarbodiimide, 4-dimethylaminopyridine and anhydrous DMF is 2.2-3.4:5-6:11-13:4.6-5.6:80-90.

9. The high-performance solid waste-based grouting material according to claim 1, characterized in that: The composite expansion agent is prepared by mixing ettringite and calcium oxide in a mass ratio of 1-2:

1.

10. A method for preparing a high-performance solid waste-based grouting material according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step S1, adding silicate cement, modified admixture, functional filler and aggregate into a photoinitiator solution, irradiating with ultraviolet light for 12-16 minutes, controlling the irradiation temperature to 62-66° C., continuing to stir and react for 7-9 hours, and after the reaction is completed, rotary evaporation, washing and drying to obtain monomer A; Step S2, mixing a polycarboxylate water-reducing agent, a composite expansion agent and a defoaming agent, and stirring them evenly to obtain a monomer B; Step S3, mixing monomer A and monomer B, stirring evenly to obtain a premix, adding the premix into deionized water, stirring evenly to obtain a high-performance solid waste-based grouting material.

Citation Information

Cited By

  • Alkali residue solid waste light-weight flow state castable for highway and preparation method of light-weight flow state castable

    CN120349164A

  • Alkali slag solid waste lightweight fluid casting material for highway and preparation method thereof

    CN120349164B

  • Solid-waste-based nano composite grouting material and preparation method thereof

    CN121107799A

  • Solid waste-based phase change aggregate and preparation method thereof

    CN122059629A

  • Solid waste-based phase change aggregate and preparation method thereof

    CN122059629B